Balanced Nutrition in School-Age Children in Pamengkang Village, Kramatwatu District, Serang Regency, Banten - Ardayani, Tri; Yogisutanti, Gurdani; Fuadah, Fahmi; Sitorus, Neti; Hotmaida, Linda (CV Media Inti Teknologi, 2023)
Health development in Indonesia is significant. One of the efforts that needs to be made is to improve the quality of humans and society in order to produce superior human resources. This community service activity aims to increase knowledge about nutrition and overcoming nutritional problems in Pamengkang village, Kramatwatu District, Serang Regency, Banten Province. The method of community service is carried out by means of counseling, lectures, and questions and answers. The media used are televisions and laptops to display material in the form of power points. The data analysis technique carried out is qualitative descriptive analysis. The data collection techniques used are observation and documentation. Community service activities carried out at SD Pamengkang, Kramatwatu District, Serang Regency, Banten Province ran smoothly and quite effectively, so as to increase the understanding of both students and teachers at the school, there should be follow-up efforts related to the application of consuming balanced nutrition daily by students. So that it can measure the level of effectiveness of this giantity.